Isolation and identification of Magnusiomyces capitatus as a lipase-producing yeast from olive mill wastewater - Salgado, Vera (2019)
ABSTRACT: Olive mill wastewaters (OMW) are effluents originated from olive oil extraction. As an oil-rich residue, OMW is a potential source of lipase-producing microorganisms and a complex medium potentially suitable for lipase production. The aim of the present study was to isolate yeasts with the ability to produce extracellular lipases from OMW. Thirty-two yeast isolates were obtained and screening for esterase/lipase activity using rapid plate detection methods allowed the selection of five isolates. Subsequently, extracellular lipolytic activity was determined in shake-flasks, and the best activity was found in the isolate JT5 (0.85 U/mL). This isolate was identified as Magnusiomyces capitatus by DNA sequencing. Growth and lypolytic activities by M. capitatus JT5 were assessed in undiluted OMW, and optimization of lipase production was achieved by a positive interaction of two factors (oxygen availability and nitrogen concentration). The highest lipase activity (1.4 U/mL) was obtained at NH4Cl concentration of 2.8 g/L and kLa of 0.65 min−1. The growth of M. capitatus JT5 in a stirred tank bioreactor, using undiluted OMW, allowed the improvement of lipase production (up to 3.96 U/mL) by increasing olive oil concentration in the medium, under the selected conditions of nitrogen concentration and oxygen availability. This study highlighted the isolate M. capitatus JT5 as a lipase-producing microorganism that is able to grow in undiluted OMW under controlled conditions. Results obtained in shake-flasks have been reproduced satisfactorily in the stirred tank bioreactor.